Management - Robbins, Stephen P. (Pearson, 2021)
PART 1: INTRODUCTION TO MANAGEMENT 1. Managers and You in the Workplace 2. Making Decisions PART 2: BASICS OF MANAGING IN TODAY'S WORKPLACE 3. Influence of the External Environment and the Organization's Culture 4. Managing in a Global Environment 5. Managing Diversity 6. Managing Social Responsibility and Ethics 7. Managing Change and Disruptive Innovation PART 3: PLANNING 8. Foundations of Planning 9. Managing Strategy 10. Entrepreneurial Ventures PART 4: ORGANIZING 11. Designing Organizational Structure 12. Managing Human Resources 13. Managing Groups and Teams PART 5: LEADING 14. Managing Communication 15. Understanding and Managing Individual Behavior 16. Motivating Employees 17. Being an Effective Leader PART 6: CONTROLLING 18. Controlling People and Operations